African Organised Crime, Transnational Crime and Terrorism: Assessing Areas of Convergence in Operational/Organisational Methods - Prof. Tunde Agara; Dr. Cyriacus, Ndukwe Ike; Dr. Esuga, (Indian Journal of Social Science and Literature (IJSSL), 2025)
Organised criminality in its various forms and sizes — mafias, syndicates, criminal gangs, cartels, cybercrime operators exploring internet spaces, or terrorists — has since the new millennium globalised in its operational and organisational structure, warranting the kind of robust scholarly research. Organized crime and terrorism in general have designated the African society with pigmentation of economic disorganization, erosion of moral and social values, and near state failure status. African organised crime, transnational crime, and terrorism are examined in the theoretical context of this work, including the 'strain of anomie', subcultures, and social disorganisation theory, to identify similarities in dimensions, culture, structure, and operational methodologies with similar crimes in the developed world. Additionally, to explore the dynamics of safety nets that African states and societies can leverage for their security. The study employed a time series research design and utilised secondary data collection through documentary review research, examining data from published materials such as books, journals, and memoirs. The theoretical study yielded results indicating that terrorism and African organized crimes are products of social structure, which emphasizes economic success – 'pathological materialism,' and the erosion of values and legitimate social constraints means to acquiring wealth. Findings also reveal a significant impact of organised crime on governance processes, the rule of law, and the overall economic structure and development. Furthermore, it is discovered to harm the law enforcement and judicial systems of states, especially in issues related to cross-border criminal networks. The study concludes that, besides the synergy of organisation that exists in criminal behaviour among organized crimes and terrorism, African organized crime is incubated within the environment of a poor governance system and social disorientation.